Aumento de la Disponibilidad Mediante la Implementación de un Plan de Mantenimiento Preventivo a las Maquinarias de la Empresa Atlanta Metal drill s.a.c. - Ramos Sparrow, Julio Oswaldo (2018)
This research paper describes the implementation of a preventive maintenance plan for the critical machines and equipment involved in the production process of the Atlanta Metal Drill SAC company, guaranteeing an increase in the operational availability of the equipment of the workshop Of the company, in an efficient and safe way. In order to meet this objective, it was necessary to collect information on the history of failure times of all the machines in the area of master, being a total of 23 machines with which the company has such as lathes, milling machines, boring machines, welding machines, Compressors, crane bridges and drills. The machines under study were subjected to a criticality analysis, resulting in four critical machines due to their higher incidence of failures: vertical lathe lathe lathe and boring machine. The maintenance indicators were then calculated, obtaining a low availability, but after the implementation of the preventive maintenance plan, it was possible to increase the availability of critical machines by more than 10%, ie the parallel lathe From 83.33% to 93.84%; The milling machine from 84.72% to 94.79% and the boring machine from 86.97 to 96.96, thus improving the performance of the machines. Through the development of the methodology for the preventive maintenance plan throughout the development of the thesis were determined the following basic points such as  Maintenance indicators  Comparison of maintenance indicators  Economic evaluation to determine that the development of this thesis through the preventive maintenance plan is really feasible